Micro- and submicrostructural Changes of Anterior Abdominal Wall Tissues as a Choice Factor of Hernioplasty for the Treatment of Ventral Postoperative Hernias - Andryushchenko V.; Bisyarin Y.; Kushnirchuk M. (Львівський клінічний вісник)
Introduction. Postoperative ventral hernias form one of the most relevant sections of modern herniology, since their prevalence in the overall structure of the anterior abdominal wall hernias tends to increase, and the results of the surgical treatment are not always optimal. In the determining the method of surgical treatment, various factors, including morphological changes in the muscular and aponeurosis structures in the area of ​​the hernia defect, are taken into account. However, in-depth study of structural violations of the tissues of different layers of the anterior abdominal wall using a combination of light and electron microscopy with the subsequent use of the information obtained to solve tactical tasks, in particular, the choice of hernioplasty method, only isolated messages are devoted. Aim. To find out the features of micro- and submicructural disorders of tissues of different layers of the anterior abdominal wall in the area of ​​the hernia defect of the anterior abdominal wall as a factor for choosing the method of hernioplasty. Materials and methods. Surgical treatment was performed on 161 patients with postoperative ventral hernia from 21 to 84 years old (108 women, 53 men). The distribution of patients with the size of the hernial gates was carried out according to the classification of J. P. Cevrel and A. M. Rats (SWR-classification). The proportion of the patients that dominated was made by the persons with median hernias and destroyed or removed navel during the previous operation. Patients with the size of the hernial gates W2-W3 predominated – 77.6% of observations. In 30 patients the histological examination of the tissue layers material of the anterior abdominal wall in the area of ​​the hernia defect using light microscopy was provided, electron microscopic study was conducted in 7 patients with material obtained during the surgical intervention. Results. Significant morphological changes in all layers of the anterior abdominal wall tissues were found. Marked atrophy of all the components of the epidermis and dermis with sclerosis and hyalinosis of vessels, increase of the amount of connective tissue with angiomatosis and sclerotic changes of intramuscular symplasts, significant qualitative and quantitative changes in aponeurosis collagen component were observed. The profundity of the structural changes that reflected the ability/inability of the tissues to regenerate and repair correlated with the clinical indicators – elderly and senile age, female, III–IV degree obesity, diabetes and severe accompanying somatic pathologies. Conclusions. Established structural changes of the anterior abdominal wall are among the significant factors for the choice of the type of hernioplasty with autologous tissues or using the alloplastic materials.